Lost in Music: Popular Music, Film and Multiculturalism - Stratton, Jon (John Libbey, 2005)
Dogs in Space (dir: Richard Lowenstein) was released in 1986, at the height of the Hawke Labor government's concern with implementing the population management policy of multiculturalism. The institutional structures that gave shape to the policy were founded on the recommendations of The Review of Post Arrival Programmes and Services to Migrants, usually known as the Galbally Report after the chair of the committee which provided it, Frank Galbally. The Galbally Report was tabled in Federal Parliament in 1978, the same year in which Dogs in Space is set. However, the idea of multiculturalism in Australia was not new. Al Grassby, then Gough Whitlam's Minister for Immigration, had delivered his speech entitled 'A Multi-Cultural Society for the Future' in 1973.The institutional signs of the breakdown of the Australian incorporatist ideology of assimilation can be found much earlier, in the establishment of the Italian welfare organisation Co.As.It in 1967 and the Greek welfare society in 1969 (Castles et al, 1988: 60). Whitlam's government set up the Australia Assistance Plan which, as Jean Martin describes it in The Migrant Presence (quoted in Castles et al: 61), provided the vehicle by which the scattered groups of migrant and migrant-oriented welfare organisations could move towards the centres of political power and also acted as a catalyst to the development of more integrated and articulate migrant organizations. In 1974 the Ethnic Community Councils of South Australia and Victoria were formed, that of New South Wales came a year later. What has all this to do with a film about a punk household in inner city Melbourne?In this chapter I will be concerned primarily with the diegetic use of popular music, and not with underscored music used for atmosphere and to link scenes. I want to examine how the organisation of popular music, in an Australia dominated by official multicultural policy, is reproduced through the way music is used in films that we might loosely call multicultural--films that have non-Anglo-Celts as their main characters.